Once-daily versus multiple-daily dosing with intravenous aminoglycosides for cystic fibrosis - Smyth, Alan R.; Bhatt, Jayesh (Wiley, 2014)
Background: People with cystic fibrosis, who are chronically colonised with the organism Pseudomonas aeruginosa, often require multiple courses of intravenous aminoglycoside antibiotics for the management of pulmonary exacerbations. The properties of aminoglycosides suggest that they could be given in higher doses less often. Objectives: To assess the effectiveness and safety of once-daily versus multiple-daily dosing of intravenous aminoglycoside antibiotics for the management of pulmonary exacerbations in cystic fibrosis. Search methods: We searched the Cystic Fibrosis Specialist Register held at the Cochrane Cystic Fibrosis and Genetic Disorders Group’s editorial base, comprising references identified from comprehensive electronic database searches, handsearching relevant journals and handsearching abstract books of conference proceedings. Date of the most recent search: 25 November 2013. Selection criteria: All randomised controlled trials, whether published or unpublished, in which once-daily dosing of aminoglycosides has been compared with multiple-daily dosing in terms of efficacy or toxicity or both, in people with cystic fibrosis. Data collection and analysis: The two authors independently selected the studies to be included in the review and assessed the risk of bias of each study. Data were independently extracted by each author. Authors of the included studies were contacted for further information. As yet unpublished data were obtained for one of the included studies. Main results: Fifteen studies were identified for possible inclusion in the review. Four studies reporting results from a total of 328 participants were included in this review. All studies compared once-daily dosing with thrice-daily dosing. One study had a low risk of bias for all criteria assessed; the remaining three included studies had a high risk of bias from blinding, but for other criteria were judged to have either an unclear or a low risk of bias. There was no significant difference between treatment groups in: forced expiratory volume at one second, mean difference 0.33 (95% confidence interval -2.81 to 3.48); forced vital capacity, mean difference 0.29 (95% confidence interval -6.58 to 7.16); % weight for height, mean difference -0.82 (95% confidence interval -3.77 to 2.13); body mass index, mean difference 0.00 (95% confidence interval -0.42 to 0.42); or in the incidence of ototoxicity, relative risk 0.56 (95% confidence interval 0.04 to 7.96). The percentage change in creatinine significantly favoured once-daily treatment in children, mean difference -8.20 (95% confidence interval -15.32 to -1.08), but showed no difference in adults, mean difference 3.25 (95% confidence interval -1.82 to 8.33). Authors’ conclusions: Once- and three-times daily aminoglycoside antibiotics appear to be equally effective in the treatment of pulmonary exacerbations of cystic fibrosis. There is evidence of less nephrotoxicity in children.